Economic analysis of hemodialysis and urgent-start peritoneal dialysis therapies - Brabo, Alexandre Minetto [UNESP]; Dias, Dayana Bitencourt [UNESP]; Silva, Everton Nunes da; Ponce, Daniela [UNESP] (FapUNIFESP (SciELO), 2025)
INTRODUCTION: Unplanned initiation of renal replacement therapy (RRT) in chronic kidney disease (CKD) patients is a common situation worldwide. In this scenario, peritoneal dialysis (PD) has emerged as a therapeutic option compared to hemodialysis (HD). In planned RRT, the costs of PD are lower than those of HD; however, the literature lacks such analyses when initiation is urgent. OBJECTIVE: To clinically and economically evaluate, from the perspective of the Unified Health System (SUS, Sistema Único de Saúde), the strategy of initiating unplanned RRT using HD or PD in patients during their first year of therapy. METHODOLOGY: Quasi-experimental study with cost-effectiveness analysis based on primary data from incident patients on RRT, over a twelve-month follow-up period, using the intention-to-treat approach. Data collection occurred prospectively, directly from medical records, computing data on the use of dialysis therapy, high-cost medications, procedures in dialysis accesses and recorded events. Costs were estimated using the amounts reimbursed by the SUS. In the economic analysis, the application of the bootstrap method and the construction of graphical representations were proposed. RESULTS: At the end of one year, there were no differences between costs and effectiveness when initiating unplanned RRT using either PD or HD. CONCLUSION: Starting RRT with PD is a similar option to starting with HD in patients requiring unplanned methods. The minimal initial investment required to establish PD slots makes it a strong option as a public health policy for expanding RRT in developing countries.